Effects of transcutaneous electrical nerve stimulation on fetal and placental development in an experimental model of placental insufficiency. (17th January 2016) - Guimarães, Camila S. O.; Gomes, Bruno B. F.; Oliveira, Rafael A.; Yamamoto, Leandro R.; Rocha, Laura P.; Glória, Maria A.; Machado, Juliana R.; Câmara, Niels O. S.; Reis, Marlene A.; Corrêa, Rosana R. M.
Abstract: Objective : To elucidate the effects of transcutaneous electrical nerve stimulation (TENS) in pregnancies with placental insufficiency. Methods : Pregnant rats were subjected to uterine artery ligation and to TENS according to the following groups: ligated stimulated (LS); ligated non-stimulated (LN), control stimulated (CS); and control non-stimulated (CN). Fetal external measurements, such as crown–rump length (CRL), fronto-occipital distance (FOD), thoracic ventral-dorsal (TVDD) and abdominal ventral-dorsal (AVDD) distances were analyzed together with the area occupied by fetal internal organs. Glucose transporter 1 (GLUT-1) expression was evaluated by immunohistochemistry in fetal organs. Thickness of junctional, labyrinth and intermediate placental zones was analyzed by morphometric evaluation in HE-stained slides, and placental hypoxia-inducible factor 1 alfa expression was measured by real-time polymerase chain reaction. Results : In LN and CS groups compared to the CN group, CRL was reduced (27.51/28.95 versus 30.16 mm), as well as FOD (6.63/6.63 versus 7.36 mm), AVDD (7.38/8.00 versus 8.61 mm) and TVDD (6.46/6.87 versus 7.23 mm). Brain GLUT-1 expression was higher in LS (1.3%) and CS (1.8%). The area occupied by placental vessels in the labyrinth zone (29.67 ± 3.51 versus 20.83 ± 7.63) and intermediate zone (26.46 ± 10.21 versus 10.86 ± 8.94) was larger in the LS group than in the LN group. Conclusions : Our results suggest a negative effect of TENS on placental development, thus compromising the maintenance of adequate blood flow to the fetus.